2004
DOI: 10.1177/1077801204265551
|View full text |Cite
|
Sign up to set email alerts
|

Abuse During Pregnancy in Industrialized and Developing Countries

Abstract: Abuse during pregnancy has increasingly been identified as an important problem with significant consequences for maternal and infant health, particularly in North America. The authors review available evidence of the prevalence and consequences of abuse during pregnancy, including maternal mortality, outside of North America. The range of prevalence found in developing countries is much wider (3.8% to 31.7%) than that of industrialized countries (3.4% to 11%), which is much closer to findings from North Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
161
2
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(194 citation statements)
references
References 65 publications
13
161
2
12
Order By: Relevance
“…18 Several previous studies have found that violence may be more likely during a first pregnancy, because the stress of transition to parenthood can trigger intimate partner violence during pregnancy, 37 and because young pregnant women may be less emotionally ready for pregnancy and more economically dependent on their partners. 38 Other work indicates that violence during pregnancy may simply be a continuation of pre-existing intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Several previous studies have found that violence may be more likely during a first pregnancy, because the stress of transition to parenthood can trigger intimate partner violence during pregnancy, 37 and because young pregnant women may be less emotionally ready for pregnancy and more economically dependent on their partners. 38 Other work indicates that violence during pregnancy may simply be a continuation of pre-existing intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…14 Comparable population-based data on the prevalence of intimate partner violence during pregnancy are lacking. Available estimates vary widely, from about 3% 15 to 30%, 1,[16][17][18] Most studies on prevalence have come from small clinical samples in maternity wards, 16 which often serve particular patient groups and communities, such as immigrant or minority groups, 19 rural communities, 20 adolescents, 21 and women from affluent areas. 22 A number of other studies include participants from rural and urban areas of the USA, 23 Canada, 24 Peru, 25 Mexico, 17 Rwanda, 26 Nigeria, 27 Saudi Arabia, 28 Iran, 16 as well as from India, 29 Pakistan, 30 UK, 15 and New Zealand.…”
mentioning
confidence: 99%
“…19, n o 1 un facteur déclencheur ou aggravant de la violence conjugale (Jasinski, 2004). L'effet le plus connu de cette violence étant le risque de donner la mort à la mère et au foetus (Parson et Harper, cités dans Campbell, 2002 ;Campbell, García-Moreno et Sharps, 2004).…”
Section: Problématiqueunclassified
“…De modo geral, apesar do amplo espectro de prevalências encontradas no mundo (Gazmararian et al,1996;Jasinski, 2004;Campbell et al, 2004), muitos estudos têm revelado que o fenômeno é freqüente e responde por número importante de agravos à saúde. Moraes e Reichenheim (2002), por exemplo, estimam que 18,2% de uma amostra de 526 mulheres no puerpério, internadas em três maternidades públicas do Rio de Janeiro, sofreram violência física durante a gestação.…”
Section: Lista De Quadrosunclassified
“…Acrescenta-se a isso o fato de que, em muitos estudos, grande parte das mulheres relatou que o padrão da violência permaneceu o mesmo, ocorrendo antes, durante e depois da gestação (Campbell, 2004;Jasinski, 2004).…”
Section: Lista De Quadrosunclassified